Improving Student's Science Literacy Capabilities Through Utilizing the Natural Environment - Fatmawati Fatmawati; Yusrizal Yusrizal; Ali Mustadi; Yunus Abidin (Jurnal Penelitian Pendidikan IPA, 2023)
In the learning process, the teaching method becomes a determining factor for the achievement of learning objectives. Basically, every student learning must play an active role in identifying problems, digging information thoroughly, and being able to provide information. The purpose of this research is to see whether the method of utilizing the natural environment can improve students' scientific literacy skills. This study uses Classroom Action Research which was carried out in 2 cycles involving 25 fifth grade students of SD PAB 22 Kelambir Lima. Data collection in this study used student activity observation sheets and student science literacy tests. Quantitative data were analyzed using descriptive statistics to see the average results obtained on the student's scientific literacy ability test. The results of this study indicate that there is an increase in students' learning activities classically which obtained the active category from the first cycle which reached 60.25% and the second cycle to 90.5%.Â